Comparison of different wheelchair seating on thermoregulation and perceptual responses in thermoneutral and hot conditions in children. Issue 3 (August 2019) - Hodges, Gary J.; Mallette, Matthew M.; Rigby, Alan; Klentrou, Panagiota; Cheung, Stephen S.; Falk, Bareket
Abstract: We examined the effects of 4 different wheelchair seatings on physiological and perceptual measures in 21 healthy, pre-pubertal children (9 ± 2 years). Participants were able-bodied and did not regularly use a wheelchair. Participants sat for 2 h in Neutral (∼22.5 °C, ∼40%RH) and Hot (∼35 °C, ∼37%RH) conditions. Four seating technologies were: standard incontinent cover and cushion (SEAT1); standard incontinent cover with new cushion (SEAT2) were tested in Neutral and Hot; new non-incontinent cover with new cushion (SEAT3); new incontinent cover and new cushion (SEAT4) were tested in Neutral only. Measurements included skin blood flow (SkBF), sweating rate (SR) and leg skin temperature ( T legB ) on the bottom of the leg ( i.e. skin-seat interface), heart rate (HR), mean skin temperature, tympanic temperature, thermal comfort, and thermal sensation. During Neutral, SkBF and T legB were lower (∼50% and ∼1 °C, respectively) and SR higher (∼0.5 mg cm −2 ·min −1 ) ( p  < 0.05) with SEAT3 compared to all other seats. SkBF was ∼30% lower ( p  < 0.05) for SEAT2 and SEAT4 compared to SEAT1. No other differences were observed between SEATs (all p  > 0.05). During Hot, HR and temperatures were higher than in Neutral but there were no differences ( p  > 0.05) between SEATs. New cover and cushion improved thermoregulatory responses during Neutral but not Hot. An impermeable incontinent cover negated improvements from cushion design. Seat cover appears more important than seat cushion during typical room conditions. Highlights: 4 different wheelchair seats on physiological and perceptual measures in children. A newly designed seat is described, with improved thermoregulatory responses. The seat is beneficial in neutral but not in hot conditions. An impermeable incontinent cover negated beneficial effect of breathable cushion.